THE COMPETENCE OF AGAMA COURT AND ITS RELATION WITH THE PROTECTION OF CHILDREN’S RIGHTS (STUDY OF MARRIAGE DISPENSATION IN THE CLASS I-B AGAMA COURT KISARAN) - Diana Evrina Nasution; Andoko; T. Riza Zarzani (RADJA PUBLIKA, 2026)
This article aimed to examine the legal position of Agama Court in their authority to determine marriage dispensations at the Kisaran Class I-B of Agama Court. By using normative legal research methods, collecting data obtained from library sources. This research found that a marriage dispensation is a legal space to ensure legal justice for the community to obtain legal certainty for marriages conducted under the age of 19, as stipulated in the Indonesian Marriage Law No. 1 of 1974, as Amended by Law No. 19 of 2024. The Supreme Court promulgated Perma No. 5 of 2019 concerning Guiding Adjudication of Marriage Dispensation Application, which emphasizes that, in principle that the best interests of the child are the primary consideration. Of course, the courts are seen as perpetuating child marriage. However, this judicial mechanism actually demonstrates that the courts must adjudicate properly and carefully to ensure that the principle of the best interests of the child in cases where the marriageable age limit deviates from the marriageable age, fulfilling the requirements for establishing a household.